2020
DOI: 10.1253/circrep.cr-20-0079
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death and Associated Factors in Elderly Patients With Atrial Fibrillation ― Long-Term Retrospective Study ―

Abstract: Against this background, the present study investigated differences in the clinical characteristics, prescription of OACs, incidence of death, and cause of death in elderly AF patients, and evaluated whether OACs and comorbidities are independently associated with prognosis in these patients. Methods Study Patients and Data Collection The present study was a hospital-based retrospective observational study. All patients with AF (paroxysmal or sustained) as of 2017 according to the electronic medical record (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The association of diabetes mellitus with all-cause mortality was reported in 19 studies ( 8 11 , 14 , 15 , 17 24 , 26 30 ). A random-effects model meta-analysis indicated that diabetes mellitus was associated with an increased risk of all-cause mortality (RR 1.37; 95% CI 1.23–1.53; I 2 = 95.1%, p < 0.001; Figure 3 ) compared with those without diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of diabetes mellitus with all-cause mortality was reported in 19 studies ( 8 11 , 14 , 15 , 17 24 , 26 30 ). A random-effects model meta-analysis indicated that diabetes mellitus was associated with an increased risk of all-cause mortality (RR 1.37; 95% CI 1.23–1.53; I 2 = 95.1%, p < 0.001; Figure 3 ) compared with those without diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published between 2011 and 2022. Three studies ( 19 , 21 , 27 ) were post-hoc analyses of randomized controlled trials, five studies ( 11 , 14 , 17 , 26 , 28 ) were retrospective designs, and others were prospective studies. Sample sizes ranged between 278 and 326,832, with 526,136 atrial fibrillation patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It's controversial whether sustained AF was associated with higher mortality than paroxysmal AF ( 10 , 11 , 14 , 15 ). This study indicated permanent AF was independently associated with an increased risk of all-causeortality and non-cardiovascular mortality, but not cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Such correlation needs more research to verify in the future. Some studies indicated OAC use was independently associated with a lower risk of all-cause mortality and cardiovascular mortality ( 10 , 11 , 14 , 15 ). However, our study did not show this correlation, and it may be attributed to the very low rate of anticoagulant therapy at baseline.…”
Section: Discussionmentioning
confidence: 99%